FPGA Based Torque and Flux Estimator of Direct Torque Control for Induction Machine Drives - Jidin, Aiman Zakwan; Sutikno, Tole; Jidin, Auzani; Nik Idris, Nik Rumzi (Departemen Teknik Elektro, Universitas Diponegoro, 2009)
This paper presents a new design of the torque and stator flux estimators for Direct Torque control (DTC) for Field Programmable Gate Array (FPGA) implementation, which permit very fast calculations.An alternative variable word-size approach in two’s complement fixed-point format is used for the implementation, in order to minimize calculation errors and the hardware resource usage. The simulation results of DTC model in Matlab, which performed double-precision calculations, are used as references to digital computations executed in FPGA implementation.The Hardware-in-the-loop (HIL) method is used to verify the minimal error between Matlab simulation and the experimental results, and thus the well-functionality of the implemented estimators.Keywords: FPGA, DTC, HIL